2008
DOI: 10.1103/physrevlett.100.207403
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Optical Spectrum of Water: Coordination and Electrostatic Effects

Abstract: The optical absorption of small water clusters, water chains, liquid water, and crystalline ice is analyzed computationally. We identify two competing mechanisms determining the onset of the optical absorption: Electronic transitions involving surface molecules of finite clusters or chains cause a redshift upon molecular aggregation compared to monomers. On the other hand, a strong blueshift is caused by the electrostatic environment experienced by water monomers embedded in a hydrate shell. Concerning the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 38 publications
5
106
1
Order By: Relevance
“…This behavior is mainly due to LFE, counteracting the red-shift induced by the band-gap narrowing, as an effect of intermolecular electronic interactions. [60][61][62] Moreover, contrary to the case of the d-SAM where the out-of-plane component of Im M dominates the spectrum in the considered frequency range, here Im M and Im ⊥ M show different spectral weights in specific energy regions. This is obviously related to the character of the excitations involved.…”
Section: B Optical Propertiesmentioning
confidence: 90%
“…This behavior is mainly due to LFE, counteracting the red-shift induced by the band-gap narrowing, as an effect of intermolecular electronic interactions. [60][61][62] Moreover, contrary to the case of the d-SAM where the out-of-plane component of Im M dominates the spectrum in the considered frequency range, here Im M and Im ⊥ M show different spectral weights in specific energy regions. This is obviously related to the character of the excitations involved.…”
Section: B Optical Propertiesmentioning
confidence: 90%
“…It has been suggested that a large fraction of molecules form only two strong HBs: one acceptor and one donor bond 2,152-156 . However, the"rings and chains" structure of liquid water 2 , as well as the inhomogeneous two-state model 152,157 implied by such an interpretation, have been challenged on many fronts 143,147,[158][159][160][161][162][163][164][165][166][167] and are a matter of an ongoing debate 80,143,147,[155][156][157][158][159][160][161][162][163][164][166][167][168][169][170][171][172] .…”
Section: Liquid Water a Structural And Dynamical Properties Of Lmentioning
confidence: 99%
“…30,31 The fully periodic treatment circumvents the difficult and nonunique modeling of finite clusters and embedding, necessary, e.g., in the context of the incremental scheme. [32][33][34][35] MP2 is considered to be an accurate method for nonconducting systems, as has been recently demonstrated 36,37 on a wide variety of crystals. The random-phase approximation based on the DFT reference 38 has been reported to provide similar accuracy.…”
Section: Introductionmentioning
confidence: 99%